Anisotropic thermal conductivity in carbon honeycomb. (19th March 2018) - Chen, Xue-Kun; Liu, Jun; Du, Dan; Xie, Zhong-Xiang; Chen, Ke-Qiu
Abstract: Carbon honeycomb, a new kind of 3D carbon allotrope experimentally synthesized recently, has received much attention for its fascinating applications in electronic device and energy storage. In the present work, we perform equilibrium molecular dynamics (EMD) to study the thermal transport properties of carbon honeycombs with different chirality. It is found that the thermal conductivity along the honeycomb axis ( κ x ) is three times larger than that normal to the axis ( κ z ), which shows strong anisotropy reflecting their geometric anisotropy. Lattice dynamics calculations reveal that this anisotropy stems from the orientation-dependent phonon group velocities. Moreover, when ambient temperature ( T ) increases from 200 K to 800 K, the T − 1 dependence of κ is observed due to the enhanced Umklapp scattering. The detailed phonon spectra analyses indicate phonon group velocities are insensitive to the variation of ambient temperature, and the temperature dependence of the relaxation times of low-frequency phonons (<20 THz) follows ∼ T − 1 behavior. Our results have a certain guiding significance to develop carbon honeycomb for effective thermal channeling devices.